2022
DOI: 10.3389/fcimb.2022.894678
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic next-generation sequencing provides prognostic warning by identifying mixed infections in nocardiosis

Abstract: Nocardia is an opportunistic pathogen that mainly involves immunosuppressed patients and causes a high mortality rate. As an emerging approach to detect infectious pathogens, metagenomic next-generation sequencing (mNGS) was reported in the detection of Nocardia. However, there is no evidence demonstrating the effect of mNGS on the prognosis of Nocardia infection. In this retrospective study, we included 18 nocardiosis patients. Nocardia species were detected by mNGS from their clinical samples. All the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In addition, although a previous study reported that SBP is typically a monobacterial infection ( 13 ), effective antibiotic coverage of pathogens could be limited when solely based on culture, leading to severe clinical outcomes. Our results showed that mNGS could detect a large number of samples with polymicrobial infections and the 6-month mortality of those patients significantly increased, which was consistent with recent studies ( 19 21 ). There are several possible reasons for this.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, although a previous study reported that SBP is typically a monobacterial infection ( 13 ), effective antibiotic coverage of pathogens could be limited when solely based on culture, leading to severe clinical outcomes. Our results showed that mNGS could detect a large number of samples with polymicrobial infections and the 6-month mortality of those patients significantly increased, which was consistent with recent studies ( 19 21 ). There are several possible reasons for this.…”
Section: Discussionsupporting
confidence: 93%
“…Cutadapt V2.10 (-q 25, 25 -m 50) was used to remove adapter sequences and low-quality reads. High-quality reads were mapped to the human genome (hg38, https://hgdownload.soe.ucsc.edu/downloads.html#human ) using default parameters on bwa-mem 2 V2.1, and then all unmapped reads were aligned to the NCBI nt database ( https://ftp.ncbi.nlm.nih.gov/genomes/ ) using BLAST V2.9.0 + (-task megablast -num_alignments 10 -max_hsps 1 -evalue 1e-10) ( 7 ). Alignments were required to be full-length with at least 95% sequence identity.…”
Section: Methodsmentioning
confidence: 99%
“…Results from mNGS supported the identification of multiple new pathogens. 3 , 17 , 38 , 47 Researchers used mNGS to detect single pathogens, 18 , 24 , 26 , 33 , 34 multiple pathogens, 29-31 , 39 , 48 , 42 and rare pathogens. 22 , 28 Results from mNGS were also used to correlate with clinical symptoms, 42 test specimens from patients with atypical or no symptoms, 21 , 40 , 49 and facilitate more accurate 28 and improved clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomic sequencing was used to determine associations between genotype and clinical phenotype, 46 elucidate etiologies, 23 , 41 , 43 , 44 , 46 investigate a pathogen's epidemiology by subsequent whole-genome capture, 50 and characterize clusters of divergent strains. 39 Additionally, in some cases, mNGS offered a faster turnaround time for results than traditional culture methods 29 and broader agnostic detection capabilities than nucleic acid amplification testing. 23 , 51 Overall, mNGS exhibits good sensitivity and specificity for diagnosing central nervous system infection and diagnostic performance during clinical application by assisting in identifying the pathogen.…”
Section: Resultsmentioning
confidence: 99%